Yu-Gi-Oh! GX. Vol. 7, King Atticus's true power - Kageyama, Naoyuki (Shonen Jump manga., 2011)
"James 'Crocodile' Cook, one of the four Duelists from America, eagerly challenges Atticus Rhodes to a Duel. Elsewhere, Jaden and Chazz unlock more secrets of their spirit cards, Winged Kuriboh and Light and Darkness Dragon. But their confrontation could lead to a Shadow Game that only one Duelist may survive!"--P. [4] of cover.